Research on Supplier Intelligent Portrait Construction Technology Based on Blockchain - Xie, Yutong; Wang, Xinnan; Li, Junyi; Wang, Huanjuan (2025 International Conference on Electrical Drives, Power Electronics & Engineering (EDPEE), 2025)
With the rapid development of blockchain technology, NFT, as a unique representation of digital assets, provides a strong guarantee for the authenticity, transparency and traceability of supplier information. This article begins with an overview of the fundamentals of blockchain technology and NFT and its potential in supply chain management. Then, the supplier portrait construction model based on NFT is designed in detail, including the core role of NFT in supplier portrait and the construction process. Further, this paper analyzes several application scenarios of NFT supplier portrait in supply chain management, including supplier selection and evaluation, supply chain risk warning and response, supply chain collaboration and efficiency improvement, supply chain financing and financial services, and continuous optimization and improvement. By introducing NFT technology, this paper aims to build a more efficient, transparent and secure supply chain management system, and provide new ideas and methods for enterprise supply chain management.